2000
DOI: 10.1046/j.1365-2540.2000.00740.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of native and hybrid elms in Spain using isozyme gene markers

Abstract: Two elm taxa occur naturally in the Iberian Peninsula: the Field elm (Ulmus minor) and the Wych elm (U. glabra). In addition, a third taxon, the foreign Siberian elm (U. pumila), was probably introduced in the 16th century as an ornamental tree and has spread spontaneously throughout the Peninsula. The natural hybridization between U. minor and U. pumila produced new individuals whose morphological traits appear to be mixed. Ulmus pumila, as well as its hybrids, has a high resistance to Dutch elm disease (DED)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
0
8

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 33 publications
(36 reference statements)
6
42
0
8
Order By: Relevance
“…The presented results are congruent with those obtained by studies of allozymes (Machon et al 1997), isozymes (Machon et al 1995, Cogolludo et al 2000, RAPDs and ISSRs (Coleman et al 2000, Goodall-Copestake et al 2005 and SSRs (Fuentes-Utrilla et al 2014). Although studies of the fi eld elm on the European level suggest a high degree of intrapopulation genetic diversity, they also suggest conclusions concerning the small genetic differentiation between populations belonging to different geographic regions.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The presented results are congruent with those obtained by studies of allozymes (Machon et al 1997), isozymes (Machon et al 1995, Cogolludo et al 2000, RAPDs and ISSRs (Coleman et al 2000, Goodall-Copestake et al 2005 and SSRs (Fuentes-Utrilla et al 2014). Although studies of the fi eld elm on the European level suggest a high degree of intrapopulation genetic diversity, they also suggest conclusions concerning the small genetic differentiation between populations belonging to different geographic regions.…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, in recent studies, "a popu-lation" consists of set of trees, originating from the same geographic region and the researched samples include a mixture of trees derived from clonal plantations, ex situ collections as well as DED tolerant clones and trees from parks and hedges (Machon et al 1997, Cogolludo-Agustín et al 2000. Hence, the heterogeneity of sampled material is extremely great and yet the genetic diversity and structure of natural elm populations remains unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Los resultados fueron comparados con los obtenidos por Cogolludo et al (2000) en dos poblaciones de U. minor (Madridejos, Toledo, y Casa de Campo, Madrid), y en el banco clonal de olmos del Centro Nacional de Mejora Genética Forestal Puerta de Hierro, Madrid. La población de Rivas-Vaciamadrid se sitúa claramente separada de las otras poblaciones estudiadas (Fig.…”
Section: La Olmeda De Rivas-vaciamadrid 213unclassified
“…Furthermore, it is commonly used in elm breeding programs due to its high tolerance to the Dutch elm disease (Smalley andGuries 2000, Mittempergher andSantini 2004). Today, U. pumila is considered as naturalized or even invasive in 43 states of the U.S., as well as in Canada (Kartesz 2011, USDA andNRCS 2011), Mexico (Todzia and Panero 1998), Argentina (Mazia et al 2001, Zalba andVillamil 2002), Spain (Cogolludo-Agustín et al 2000), the European part of Russia, Estonia and Australia (NOBANIS 2012). Webb (1948) reported that different Chinese origins of the Siberian elm are characterized by differing frost hardiness.…”
Section: Introductionmentioning
confidence: 99%